Assessment of self‐rated health 5 years after Roux‐en‐Y gastric bypass for severe obesity. Issue 6 (30th September 2019) - Sandvik, J.; Hole, T.; Klöckner, C. A.; Kulseng, B. E.; Wibe, A.
Abstract : Background: Patients' perceptions of health change after bariatric surgery are complex. The aim of this study was to explore whether self‐rated health (SRH), a widely used tool in public health research, might be relevant as an outcome measure after Roux‐en‐Y gastric bypass (RYGB) for severe obesity. Methods: This was a single‐centre retrospective study of a local quality registry. SRH score was registered at baseline and 5 years after RYGB. SRH, one of the 36 items in the quality‐of‐life Short Form 36 (SF‐36®) questionnaire, is the answer to this single question: 'In general, would you say your health is excellent (1), very good (2), good (3), fair (4) or poor (5)?' Change in SRH was analysed in relation to change in weight, co‐morbidities and quality of life after 5 years. Results: Of a total of 359 patients who underwent RYGB between September 2006 and February 2011, 233 (64·9 per cent) reported on SRH before and 5 years after surgery. Of these, 180 (77·3 per cent) were women, and the mean(s.d.) age was 40(9) years. Some 154 patients (66·1 per cent) reported an improvement in SRH, 60 (25·8 per cent) had no change, and SRH decreased in 19 patients (8·2 per cent). SRH in improvers was related to better scores in all SF‐36® domains, whereas SRH in non‐improvers was related to unchanged or worsened scores in all SF‐36® domains except physical function. Conclusion: Two‐thirds of patients reported improved SRH 5 years after RYGB for severe obesity. In view of its simplicity, SRH may be an easy‐to‐use outcome measure in bariatric surgery. Abstract : A single question on self‐rated health (SRH) could provide an easy‐to‐use outcome measure in bariatric surgery. Two‐thirds of patients who had Roux‐en‐Y gastric bypass for severe obesity reported improved SRH after 5 years. Self‐rated health ‐ One question to replace a questionnaire? Abstract : Antecedentes: Las percepciones de los pacientes del cambio de su salud tras la cirugía bariátrica son complejas. El objetivo de este estudio fue examinar si la autovaloración de la salud ( self‐rated health, SRH), una herramienta ampliamente utilizada en investigación en salud pública, podría ser relevante como medida de resultado después del bypass gástrico en Y de Roux ( Roux‐en‐Y gastric bypass, RYGB) para la obesidad severa. Métodos: Se llevó a cabo un estudio retrospectivo de un registro de calidad local de un único centro. La SRH se recogió en situación basal y a los 5 años tras el RYGB. SRH es una de las 36 preguntas del cuestionado de calidad de vida SF‐36 (forma corta) y consiste en la respuesta a esta única pregunta: "En general, diría que su salud es excelente (1), muy buena (2), buena ( 3), razonable (4) o pobre (5)?". Resultados: De un total de 359 pacientes sometidos a un RYGB en el periodo entre septiembre de 2006 y febrero de 2011, 233 (65%) informaron del SRH antes y a los 5 años de la cirugía. De ellos, 180 (77, 3%) eran mujeres y la edad media era de 40 (DE 9) años. La SRH mejoró en 154 (66, 1%) pacientes, no experimento cambios en 60 (25, 8%) y disminuyó en 19 (8, 2%). En tanto que la mejoría de la SRH se relacionó con mejores puntuaciones en todos los dominios de cuestionario SF‐36, la no mejoría se relacionó con puntuaciones iguales o peores en todos los dominios del SF‐36, a excepción de la función física. Conclusión: Dos tercios de los pacientes reportaron mejoría de la SRH a los 5 años tras un RYGB por obesidad grave, y debido a su simplicidad, la SRH podría constituir una medida de resultado, de fácil uso, en cirugía bariátrica.